Magnetically separable (Fe, Mn) Al2O4 catalyst material capable of simultaneously enhancing adsorption and decomposition of ozone as well as preparation method and application of magnetically separable (Fe, Mn) Al2O4 catalyst material

The (Fe,Mn)Al2O4 catalytic material prepared by two-step hydrothermal method uses the iron-manganese oxide coexistence structure to improve the ozone adsorption and decomposition capabilities, solves the problems of waste of existing catalyst resources and insufficient activity, and achieves efficient degradation of organic pollution and avoid environmental pollution through magnetic separation.

CN119186586AActive Publication Date: 2024-12-27ZHEJIANG UNIV OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411421063.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-27
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing catalysts have problems such as waste of resources, limited catalytic activity, insufficient adsorption capacity and difficulty in recycling in ozone oxidation, which limits their efficient removal ability of new organic pollutants in degraded water bodies.

Method used

A two-step hydrothermal method is used to prepare (Fe,Mn)Al2O4 catalytic material. This material improves the adsorption and decomposition ability of ozone through the coexistence structure of iron and manganese oxides, and realizes easy recovery of the catalyst through magnetic properties.

Benefits of technology

It significantly improves the adsorption and decomposition ability of ozone, enhances the degradation efficiency of organic pollutants, and avoids the loss of catalysts through magnetic separation function to pollute the environment, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186586A_ABST
    Figure CN119186586A_ABST
Patent Text Reader

Abstract

The invention relates to a magnetically separable (Fe, Mn) Al2O4 material capable of simultaneously enhancing adsorption and decomposition of ozone and a preparation method and application thereof, and the process is as follows: adding Al2O3 into a NaOH solution, uniformly stirring, transferring into a PTFE hydrothermal reactor, and carrying out hydrothermal reaction in a drying oven; dissolving the obtained NaAlO2 powder in deionized water, adding hydrochloric acid, uniformly stirring, and marking the solution as a solution A after the solution becomes clear from turbid; mixing ferric nitrate, manganous nitrate and deionized water, and marking as a solution B; mixing the solution A and the solution B, dropwise adding ammonia water until the pH value is 10-11, and uniformly stirring; transferring into a PTFE (Polytetrafluoroethylene) hydrothermal reactor, and carrying out hydrothermal reaction in a drying oven; and after the reaction, centrifugally washing the material, drying and heating to obtain the (Fe, Mn) Al2O4 material. The preparation method is simple and low in cost, the prepared material can strengthen adsorption and decompose ozone to generate free radicals and rapidly degrade organic pollutants at the same time, separation and fixation can be achieved through magnetism after catalytic ozonation of the pollutants is completed, secondary pollution is avoided, and the material can be applied to degradation of the organic pollutants in tap water or town sewage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is a material preparation and chemical catalytic decomposition technology, and relates to a catalyst for catalyzing ozone to efficiently degrade organic pollutants, a preparation method and an application thereof. The catalyst can simultaneously enhance the adsorption and decomposition of ozone to degrade organic matter and can magnetically separate the organic matter after degrading it. Background Art

[0002] In recent years, new organic pollutants such as antibiotics have been frequently detected in aquatic environments, and these pollutants pose a serious threat to aquatic organisms and aquatic products. The continuous input of new pollutants into the environment leads to the rapid accumulation of pollutants in water, and causes potential and irreversible harm to humans through the food chain. Antibiotics in the water environment mainly come from urban sewage, hospital sewage, recycled wastewater and wastewater discharged by the pharmaceutical industry, most of which are organic pollutants that are difficult to biodegrade. Therefore, it has become an urgent problem to develop a technology that can effectively remove or decompose organic pollutants in tap water or urban wastewater to eliminate the harm of these pollutants to the human body or various organisms. At present, the main methods for degrading and treating new organic pollutants in water bodies include conventional water treatment technology, activated carbon adsorption, chemical oxidation, membrane separation, etc.

[0003] Ozone oxidation is a type of chemical oxidation method. It is a common and effective treatment method for removing new organic pollutants from water. However, the single ozone oxidation method is selective and will only degrade and remove certain organic matter that is easily oxidized by ozone. The use of catalysts to catalyze ozone to produce free radicals such as hydroxyl radicals can effectively degrade most new organic pollutants in water.

[0004] The long-term, efficient and stable processing capacity of the ozone catalytic oxidation process depends largely on the selected catalyst material. In traditional catalyst applications, we often face some challenges and limitations. First, the catalyst is difficult to recover after the reaction, which not only causes a waste of resources, but also may cause environmental pollution due to the loss of the catalyst. Secondly, the catalytic activity of some catalysts is limited, and they may need to be used under harsh conditions to achieve the best effect, which undoubtedly increases production costs and energy consumption. In addition, the limited adsorption capacity of the catalyst for ozone makes it impossible to achieve efficient catalytic oxidation at low concentrations. The above shortcomings undoubtedly greatly limit their practical application. Therefore, it is necessary to seek a catalyst with good catalytic ozone and efficient degradation of organic pollutants. Summary of the invention

[0005] The purpose of the present invention is to provide a simple and easy-to-operate method for preparing a (Fe, Mn)Al2O4 material which can simultaneously enhance the adsorption and decomposition of ozone and can be magnetically separated.

[0006] The mechanism of traditional iron oxide or manganese oxide decomposing ozone is: ozone combines with the surface hydroxyl group on the metal site of the oxide to obtain an electron, then decomposes, and at the same time causes the valence state of the metal site to increase. The mechanism of traditional alumina decomposing ozone is that ozone is adsorbed on the metal site (Lewis acid site) on the aluminum surface and then decomposed. However, the above two materials have the following problems when decomposing ozone alone: ​​after the valence state of traditional iron oxide or manganese oxide increases, it cannot be reduced in time to continue to catalyze ozone. The structure of alumina alone is relatively dense, and the metal activity exposed on the surface is too little.

[0007] The (Fe, Mn) Al2O4 catalytic material invented in this patent perfectly solves the shortcomings of the above-mentioned materials in decomposing ozone. When the three metals coexist in the crystal, in the process of decomposing ozone, the electrons lost by iron can be supplemented by manganese. The tetravalent manganese formed after manganese loses electrons has enhanced oxidation capacity, and can obtain electron supplements by oxidizing pollutants in water, so that iron-manganese oxides can obtain more electrons for decomposing ozone as a whole. At the same time, due to the presence of iron and manganese in the crystal structure, the surrounding Al is no longer restricted by the regularly grown Al-O bonds, so that more Al sites can be used for the adsorption and decomposition of ozone. In addition, the ozone adsorbed on the Al site can also be assisted in decomposition by the surrounding iron-manganese sites. Therefore, the (Fe, Mn) Al2O4 catalytic material can significantly improve the adsorption and decomposition capacity of ozone in general.

[0008] The method uses a two-step hydrothermal method to prepare (Fe, Mn) Al2O4. The preparation method is simple in process and mild in conditions, and has the triple functions of adsorbing ozone, rapidly decomposing ozone to generate free radicals to degrade pollutants, and easily separating and recovering the catalyst. The (Fe, Mn) Al2O4 catalytic material obtained by the above preparation method can be used to catalyze the efficient degradation of organic pollutants in tap water or urban sewage by ozone.

[0009] To achieve the above object, the present invention proposes a simple and easy-to-operate method for preparing a (Fe, Mn)Al2O4 catalytic material that can simultaneously enhance the adsorption and decomposition of ozone and can be magnetically separated, which is achieved by the following technical scheme: The preparation method includes the following process steps: S1: Add Al2O3 to NaOH solution and stir magnetically to make it uniform; transfer the obtained mixed solution to a PTFE hydrothermal reactor and perform a hydrothermal reaction at a certain temperature in an oven; S2: After the suspension is heated, it is taken out and naturally cooled to room temperature, and then centrifuged to separate the solid and liquid. The separated solid component is washed with deionized water several times and then placed in a vacuum drying oven to obtain NaAlO2 powder; S3: Add the obtained NaAlO2 powder to deionized water, then add hydrochloric acid and stir, and wait until the solution changes from turbid to clear, and set aside, marked as solution A; evenly mix and dissolve ferric nitrate and manganese nitrate with deionized water, marked as solution B; S4: After mixing the AB solutions, gradually add ammonia water until the pH value is maintained at 10-11 and then stir for a period of time; then transfer the solution to a PTFE hydrothermal reactor and perform a hydrothermal reaction at a certain temperature in an oven; S5: After heating, the suspension is taken out and naturally cooled to room temperature, followed by centrifugal solid-liquid separation. The separated solid components are placed in a vacuum drying oven for drying and then placed in a muffle furnace for heating to completely dehydrate and crystallize the product, thereby successfully preparing the (Fe, Mn)Al2O4 material.

[0010] Preferably, the concentration of the NaOH solution in step S1 is 10 mol / L; the usage ratio of the NaOH solution to Al2O3 in step S1 is 1 ml:20.4 mg.

[0011] Preferably, the hydrothermal temperature in step S1 is 180-190° C., and the reaction time is 30-35 h; and the hydrothermal temperature in step S4 is 180-190° C., and the reaction time is 7-10 h.

[0012] Preferably, the molar ratio of the NaAlO2 solution to the hydrochloric acid solution in step S3 is 1:1; and the stirring time after the hydrochloric acid solution is added to the NaAlO2 solution is 8-10 hours.

[0013] Preferably, the centrifugal separation conditions in steps S2 and S5 are 12,000 rpm, 5 minutes, and multiple water washes; and the magnetic stirring rate is 500-700 r / min.

[0014] Preferably, the concentrations of ferric nitrate and manganese nitrate in the mixed solution of step S3 are both 0.1 mol / L.

[0015] Preferably, in step S2, the drying time of the (Fe, Mn)Al2O4 suspension at 60-70°C is 10-12 hours.

[0016] Preferably, the muffle furnace calcination condition in step S5 is calcination at 550-600° C. for 5-8 hours and then natural cooling.

[0017] The present invention also provides a (Fe, Mn)Al2O4 catalyst material that can simultaneously enhance the adsorption and decomposition of ozone and can be magnetically separated, and is prepared by the preparation method described in any one of claims 1-8.

[0018] The present invention also proposes the use of the (Fe, Mn)Al2O4 catalyst material as described above, which can simultaneously enhance the adsorption and decomposition of ozone and can be magnetically separated, in catalyzing ozone to efficiently degrade organic pollutants. The (Fe, Mn)Al2O4 catalytic material is used to catalyze ozone to efficiently degrade organic pollutants, wherein Fe and Mn provide catalytic active sites, and Al is responsible for adsorbing ozone. The (Fe, Mn)Al2O4 after the reaction is magnetic and can be efficiently separated from the reaction liquid.

[0019] Compared with the prior art, the present invention has the following advantages: a. The (Fe, Mn)Al2O4 catalytic material prepared by the present invention is superior to commercial Al2O3 materials, commercial Fe2O3 materials and commercial MnO2 materials in catalytic ozone degradation of organic pollutants.

[0020] b. The (Fe, Mn)Al2O4 catalytic material prepared by the present invention has a strong adsorption capacity for ozone, which further enhances its activity in the degradation process, and its pollutant degradation performance is better than that of conventional catalysts.

[0021] c. The (Fe, Mn)Al2O4 catalytic material prepared by the present invention has magnetism, so that the catalyst can be easily recovered, thereby preventing the loss of the catalyst from causing pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope (SEM) image of the (Fe, Mn)Al2O4 catalytic material; Figure 2 This is the elemental composition analysis (EDS) diagram of (Fe, Mn)Al2O4 catalytic material; Figure 3 is the X-ray diffraction (XRD) pattern of (Fe, Mn)Al2O4 catalytic material; Figure 4 This is an efficiency diagram of ATZ, one of the organic pollutants, in the degradation of the present invention; Figure 5 This is a diagram of outlet ozone concentration during the ATZ degradation process of the present invention. DETAILED DESCRIPTION

[0023] The content of the present invention is further illustrated below in conjunction with specific examples, but it should not be construed as limiting the present invention. Without departing from the spirit and substance of the present invention, simple modifications or replacements made to the inventive method, steps or conditions all belong to the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.

[0024] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. Embodiment 1:

[0025] A method for preparing a (Fe, Mn)Al2O4 material that can simultaneously enhance the adsorption and decomposition of ozone and can be magnetically separated comprises the following steps: 1.02 g Al2O3 was added to 10 M NaOH solution (50 mL) and magnetically stirred for 2 h. The mixed solution was transferred to a PTFE hydrothermal reactor and hydrothermally heated in an oven at 190 °C for 35 h. After cooling, the obtained NaAlO2 was washed with deionized water several times and dried at 80 °C for 12 h to obtain NaAlO2 powder. Subsequently, 0.82 g NaAlO2 powder was added to 50 mL of water, and an equimolar ratio of hydrochloric acid was added and stirred for 8 h. After the solution changed from turbid to clear, it was set aside and marked as solution A. 0.1 mol / L iron nitrate and manganese nitrate were uniformly mixed and dissolved with 100 mL of deionized water, marked as solution B. After mixing the AB solutions, ammonia water was gradually added until the pH value was maintained at 10-11, and stirred for about 30 min. The solution was then transferred to a PTFE hydrothermal reactor and hydrothermally heated in an oven at 180 °C for 7 h. Subsequently, the material was centrifuged and washed, and then dried at 60 °C for 10 h, and then heated in a muffle furnace at 550 °C for 5 h to dehydrate and crystallize the product. Embodiment 2:

[0026] The present embodiment is different from Example 1 in that the concentrations of the ferric nitrate and manganese nitrate are both 0.2 mol / L, and the rest are the same as Example 1. Embodiment 3:

[0027] This embodiment is an application of the (Fe, Mn)Al2O4 catalytic material for catalyzing ozone to efficiently degrade organic pollutants in Example 1, which is applied to the degradation of organic pollutants in tap water or urban sewage.

[0028] The present invention is verified by the following tests: Experiment 1: This experiment is a method for preparing a (Fe, Mn)Al2O4 catalytic material, which is specifically carried out in the following steps: (Fe, Mn) Al2O4 was prepared by a two-step hydrothermal method. First, 1.02 g Al2O3 was added to 10 M NaOH solution (50 mL) and magnetically stirred for 2 h. The mixed solution was transferred to a PTFE hydrothermal reactor and hydrothermally heated in an oven at 190 °C for 35 h. After cooling, the obtained NaAlO2 was washed with deionized water several times and dried at 80 °C for 12 h to obtain NaAlO2 powder. Subsequently, 0.82 g NaAlO2 powder was added to 50 mL deionized water, and hydrochloric acid in an equal molar ratio was added and stirred for 8 h. After the solution changed from turbid to clear, it was reserved and marked as solution A. 0.1 M ferric nitrate and 0.1 M manganese nitrate were uniformly mixed and dissolved with 100 mL deionized water, marked as solution B. After mixing the AB solutions, ammonia water was gradually added until the pH value was maintained at 10-11, and stirred for about 30 min. The solution was then transferred to a PTFE hydrothermal reactor and hydrothermally heated in an oven at 180 °C for 7 h. Subsequently, the material was centrifuged and washed, then dried at 60°C for 10 h, and then heated in a muffle furnace at 550°C to dehydrate and crystallize the product for 5 h, thereby successfully preparing the (Fe, Mn)Al2O4 material. Figure 1 As shown, Figure 2 The element composition analysis diagram of the catalyst material shows that the element ratio of O element is 58.53%, the element ratio of Al element is 15.20%, the element ratio of Mn element is 12.57%, and the element ratio of Fe element is 13.69%; XRD diagram ( Figure 3 ) shows that the prepared (Fe,Mn)Al2O4 material has a high degree of crystallinity.

[0029] Experiment 2: This experiment simulates the application of a (Fe, Mn)Al2O4 catalytic material in the catalytic ozone efficient degradation of an organic pollutant, atrazine (ATZ). ATZ was dissolved in 1 L of deionized water to a concentration of 5 mm / L and loaded into the ozone catalytic reaction device. The (Fe, Mn)Al2O4 catalytic material prepared in Experiment 1 was then added to the solution of the ozone catalytic reaction device. The catalyst dosage was 0.03 g / L and the total dosage was 30 mg. Ozone was continuously aerated into the reactor, and the ozone concentration was detected at the reactor outlet. Samples were taken at regular intervals to monitor the concentration of ATZ in the simulated wastewater. Figure 4 In the figure, the zigzag lines respectively show the residual concentration of ATZ when no catalyst is added, the residual concentration of ATZ when commercial Fe2O3 with the same catalyst concentration is added, the residual concentration of ATZ when commercial Al2O3 with the same catalyst concentration is added, the residual concentration of ATZ when commercial MnO2 with the same catalyst concentration is added, and the residual concentration of ATZ when the (Fe,Mn)Al2O4 catalytic material prepared in Example 1 is added. Figure 4The results show that after 30 minutes of reaction time, 52.1% of ATZ was oxidized by ozone without adding a catalyst, 62.2% of ATZ was oxidized by ozone catalyzed by Fe2O3, 55.9% of ATZ was oxidized by ozone catalyzed by Al2O3, and 68.1% of ATZ was oxidized by ozone catalyzed by MnO2. The (Fe, Mn)Al2O4 catalytic material prepared in Example 1 catalyzed the degradation of more than 98% of ATZ within 5 minutes. Figure 5 In the figure, the zigzag lines respectively show the ozone outlet concentration when no catalyst is added, the ozone outlet concentration when commercial Fe2O3 with the same catalyst concentration is added, the ozone outlet concentration when commercial Al2O3 with the same catalyst concentration is added, the ozone outlet concentration when commercial MnO2 with the same catalyst concentration is added, and the ozone outlet concentration when the (Fe, Mn)Al2O4 catalytic material prepared in Example 1 is added. Figure 5 The results show that (Fe,Mn)Al2O4 catalytic material can catalyze the decomposition of ozone to produce free radicals.

Claims

1. A method for preparing a (Fe, Mn)Al2O4 catalyst material that can simultaneously enhance the adsorption and decomposition of ozone and can be magnetically separated, characterized in that: (Fe, Mn)Al2O4 was prepared by a two-step hydrothermal method, which specifically includes the following steps: S1: Add Al2O3 to NaOH solution and stir magnetically to make it uniform; transfer the obtained mixed solution to a PTFE hydrothermal reactor and perform a hydrothermal reaction at a certain temperature in an oven; S2: After the suspension is heated, it is taken out and naturally cooled to room temperature, and then centrifuged to separate the solid and liquid. The separated solid component is washed with deionized water several times and then placed in a vacuum drying oven to obtain NaAlO2 powder; S3: Add the obtained NaAlO2 powder to deionized water, then add hydrochloric acid and stir, and wait until the solution changes from turbid to clear, and set aside, marked as solution A; evenly mix and dissolve ferric nitrate and manganese nitrate with deionized water, marked as solution B; S4: After mixing the AB solutions, gradually add ammonia water until the pH value remains at 10-11 and then stir for a while; The solution is then transferred to a PTFE hydrothermal reactor and subjected to a hydrothermal reaction at a certain temperature in an oven; S5: After heating, the suspension is taken out and naturally cooled to room temperature, followed by centrifugal solid-liquid separation. The separated solid components are placed in a vacuum drying oven for drying and then placed in a muffle furnace for heating to completely dehydrate and crystallize the product, thereby preparing the (Fe, Mn)Al2O4 catalyst material.

2. The method for preparing a (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable according to claim 1, characterized in that: The concentration of the NaOH solution in step S1 is 10 mol / L; the usage ratio of the NaOH solution to Al2O3 in step S1 is 1 ml: 20.4 mg.

3. The method for preparing a (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable according to claim 1, characterized in that: In step S1, the hydrothermal temperature is 180-190° C., and the reaction time is 30-35 h; in step S4, the hydrothermal temperature is 180-190° C., and the reaction time is 7-10 h.

4. The method for preparing a (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable according to claim 1, characterized in that: The molar ratio of the NaAlO2 solution to the hydrochloric acid solution in step S3 is 1:1; the stirring time after the hydrochloric acid solution is added to the NaAlO2 solution is 8-10 hours.

5. The method for preparing a (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable according to claim 1, characterized in that: The centrifugal separation conditions in steps S2 and S5 are 12,000 rpm, 5 minutes, and multiple water washes; the magnetic stirring rate is 500-700 r / min.

6. The method for preparing a (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable according to claim 1, characterized in that: The concentrations of ferric nitrate and manganese nitrate in the mixed solution of step S3 are both 0.1 mol / L.

7. The method for preparing a (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable according to claim 1, characterized in that: In step S2, the drying time of the (Fe, Mn)Al2O4 suspension at 60-70°C is 10-12 hours.

8. The method for preparing a (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable according to claim 1, characterized in that: The muffle furnace calcination conditions in step S5 are calcination at 550-600° C. for 5-8 hours and then natural cooling.

9. A (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. The use of the (Fe, Mn)Al2O4 catalyst material capable of simultaneously enhancing the adsorption and decomposition of ozone and being magnetically separable in catalyzing ozone to efficiently degrade organic pollutants as claimed in claim 9, characterized in that: (Fe, Mn)Al2O4 catalytic material is used to catalyze ozone to efficiently degrade organic pollutants. Fe and Mn provide catalytic active sites, and Al is responsible for adsorbing ozone. The (Fe, Mn)Al2O4 after the reaction is magnetic and can be efficiently separated from the reaction liquid.

Citation Information

Patent Citations

  • Multiphase catalytic ozone oxidation depollution technology based on enhanced ozone adsorption and application thereof

    CN104028281A

  • Composition for reducing discharge of oxygen-deficient regenerative flue gas HN3 and HCN and preparation method thereof

    CN105126841A

  • Preparation method of high-efficiency heterogeneous Fenton catalyst MnFe2O4 / SiO2

    CN109317162A

  • Exhaust gas-purifying catalyst

    JP2013027858A

  • Removal of heavy metals and heavy metal radioactive isotopes from liquids

    US4902665A